2005
DOI: 10.1126/science.1101812
|View full text |Cite
|
Sign up to set email alerts
|

New Perspectives on Ancient Mars

Abstract: Mars was most active during its first billion years. The core, mantle, and crust formed within ∼50 million years of solar system formation. A magnetic dynamo in a convecting fluid core magnetized the crust, and the global field shielded a more massive early atmosphere against solar wind stripping. The Tharsis province became a focus for volcanism, deformation, and outgassing of water and carbon dioxide in quantities possibly sufficient to induce episodes of climate warming. Surficial and near-surface water c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
184
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 270 publications
(190 citation statements)
references
References 93 publications
4
184
0
2
Order By: Relevance
“…Olympus Mons on the Mars, the largest volcano in our Solar System is the most recent volcano in this region. Moreover, the traces of erupted lava from these volcanoes featured long from the South to the North, and it is assumed that the volcanic activities have affected the martian atmosphere (Solomon et al 2005).…”
Section: The Mars Geographymentioning
confidence: 99%
“…Olympus Mons on the Mars, the largest volcano in our Solar System is the most recent volcano in this region. Moreover, the traces of erupted lava from these volcanoes featured long from the South to the North, and it is assumed that the volcanic activities have affected the martian atmosphere (Solomon et al 2005).…”
Section: The Mars Geographymentioning
confidence: 99%
“…Volcanic activity on Tharsis has apparently continued until the very recent past, albeit at a small rate (Neukum et al 2004). The recent knowledge on Mars volcanism has been summarized by Solomon et al (2005).…”
Section: Volcanismmentioning
confidence: 99%
“…From the REE characteristics of martian meteorites, it has been shown that Mars differentiated very early in the history of the Solar System (~4.5 Ga) to form a metallic core, a silicate mantle, and a crust, and broadly differentiated to form a LREE-depleted reservoir (low La/Yb, high Sm/Nd) and an inferred, complementary LREE-enriched reservoir (high La/Yb, low Sm/Nd; [159]), the latter of which remains to be directly sampled (see discussion later; e.g., [160][161][162][163][164][165][166][167]). Unlike the lunar sample collection and the lunar magma ocean model (Figures 3 and 4), Mars lacks an Al-rich anorthositic crust.…”
Section: Rees Beyond the Moonmentioning
confidence: 99%